Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to evaluate $\lim_{x \to -N} (x+N) \Gamma(x) $ =$(-1)^N/N!$, for N = 0, 1, 2, ... but I keep getting zero.

I tried using the definition of $\Gamma(x) = \Gamma(x+1)/x $ with no luck.

Is there any identity for gamma I could use to get the desired result?

share|cite|improve this question
Using some of these ideas, and trying to formulate my own answer based off of what I actually know, I got $lim_{x \rightarrow -N} (x+N) \Gamma(x)$ = $lim_{x \rightarrow -N} (x+N) \frac{\Gamma(x+N)}{(x)_{N}}$ = $lim_{x \rightarrow -N} \frac {\Gamma(x+N+1)}{x(x+1)(x+2)...(x+N+1)}$ =$ \frac{\Gamma(1)}{(-1)[N(N-1)(N-2)...1]}$ =$\frac{1}{(-1)(N!)}$ which is still wrong I think. – renagade629 Oct 7 '12 at 6:10
up vote 2 down vote accepted

Assuming you are exposed to the Euler's reflection formula: $$ \Gamma(x) \Gamma(1-x) = \frac{\pi}{\sin(\pi x)} \tag{1} $$ we get: $$ \lim_{x \to -n} (x+n)\Gamma(x) = \lim_{x\to-n} \frac{\pi (x+n)}{\sin(\pi x)}\frac{1}{\Gamma(1-x)} \stackrel{y=x+n}{=} \lim_{y \to 0} \frac{\pi y}{\sin(\pi y - \pi n)} \frac{1}{\Gamma(1 + n -y )} $$ Using identity $\sin(\pi y - \pi n) =(-1)^n \sin(\pi y)$, valid for integer $n$, we conclude $$ \lim_{x \to -n} (x+n)\Gamma(x) = \frac{(-1)^n}{\Gamma(1+n)} \, \underbrace{ \lim_{y \to 0} \frac{\pi y}{\sin(\pi y)} }_{ \lim_{z\to 0} \frac{z}{\sin(z)}=1}= \frac{(-1)^n}{n!} $$

share|cite|improve this answer
I can follow your work easiest since this formula is in my reference sheet. I don't understand the purpose of making the y = x+n substitution. Is it necessary? Can it be done without it? For $\Gamma (1+n-y)$ it disappeared from your second line when you transitioned to the third line to $\Gamma (1+n)$. Wasn't the $sin(\pi y - \pi n) = (-1)^n sin(\pi y)$ in the denominator? How did the $(-1)^n$ get moved to the numerator? – renagade629 Oct 7 '12 at 5:47
@renagade629 There is no need to introduce $y$. I thought it would be easier. Anyway, moving $(-1)^n$ from the denominator to the numerator is done as follows: $$ \frac{1}{(-1)^n} = \frac{(-1)^n}{(-1)^{2n}}$$ but for integer $n$, $2n$ is even, and thus $(-1)^{2n} = 1$. – Sasha Oct 7 '12 at 12:41

Let $L$ denote the desired limit. Write $(x+N)\Gamma(x)=\dfrac{\Gamma(x)}{(x+N)^{-1}}$.

Recall that $\Gamma(x)$ has simple poles at the nonpositive integers, with residue at $x=-N$ equal to $l=\frac{(-1)^N}{N!}.$ Thus, near $x=-N,$ we can express $\Gamma(x)=\frac{l}{x+N}+h(x)$ with $h(x)$ holomorphic. We obtain


as desired. Of course, the real crux of the question is to prove that the residue of the gamma function at $x=-N$ is $l.$ I'll leave this to you, because it really is a nice exercise on the idea of analytic continuation.

share|cite|improve this answer
Thanks I will look into it. I am taking an undergraduate course in differential equations and we are using the gamma function for bessel ODE and we are using this notation. So I know nothing of the terminology that you used. I just have a sheet with gamma properties. – renagade629 Oct 7 '12 at 2:48
You're welcome! The important part is that $\Gamma(x)$ can be extended to a function on the complex numbers, minus the points $x=0,-1,-2,-3,\ldots.$ However, near each of these there is a Laurent expansion (like a Taylor series except allowing negative powers) of $\Gamma(x).$ So, in some small neighbourhood of $x=-N,$ we know that $\Gamma(x)=\frac{(-1)^N}{N!(x+N)}+a_0+a_1(x+N)+a_2(x+N)^2+\cdots,$ where the $a_i$ are constants. (In my answer, $h(x)=a_0+\cdots.$) This is extremely useful, used to prove identities such as Euler's reflection mentioned in another answer. – Andrew Oct 7 '12 at 3:18

Recalling the rising and falling factorials

$$ x^{(N)}=\frac{\Gamma(x+N)}{\Gamma(x)}\,,\quad (x)_N=\frac{\Gamma(x+1)}{\Gamma(x-N+1)}\,, \quad {(-a)}^{(N)} = {(-1)}^N {(a)}_{{N}}\,,$$

where $ \Gamma(x+1)= x! \,.$

$$ (x+N)\Gamma(x)= \frac{\Gamma(x)(x+N)\Gamma(x+N)}{\Gamma(x+N)}=\frac{\Gamma(x)}{\Gamma(x+N)}(x+N)!=\frac{(x+N)!}{x^{(N)}}\,,$$

$$\Rightarrow (x+N)\Gamma(x) = \frac{(x+N)!}{x^{(N)}} $$

Taking the limit of the above equation gives

$$ \lim_{n\to \infty} (x+N)\Gamma(x) = \frac{0!}{(-N)^{(N)}} = \frac{1}{(-1)^N(N)_N}= \frac{1}{(-1)^N N!}\,.$$

Note that, $(N)_N = N!\,,$ by the second identity of the falling factorial.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.